Hubungan Status Gizi dengan Trombositopenia pada Anak Demam Berdarah Dengue di RSUD Kabupaten Bekasi Periode 2022-2023 - Andayani, Sri Hastuti; Saputri, Titania Isro Mawar (Lembaga Penelitian Universitas YARSI, 2024)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus and often occurs in tropical and subtropical climates. At the end of 2022, the most cases of DHF occurred on the island of Java and Bekasi City was ranked 3rd highest in Indonesia. Children have a higher risk factor for dengue infection. Several studies have shown a correlation between nutritional status and the incidence of DHF. Children with poor nutritional status are very susceptible to dengue virus infection due to low cellular immunity. Meanwhile, excessive nutritional status can affect the severity of DHF. One of the body's responses to DHF is thrombocytopenia which is related to the severity of DHF. DHF sufferers who experience a decrease in platelet levels to <100,000 cells/mm3 have a higher risk of developing grade III DHF and Dengue Shock Syndrome. This study used an analytical observational study with a cross-sectional approach conducted on pediatric DHF patients who were treated at the Bekasi Regency Hospital between January 2022-December 2023, and had complete medical records with data in the form of height, weight, diagnosis, and platelet levels from day 5 to day 7. There were 159 DHF patients and 59 children met the inclusion criteria, with more males than females, and the highest age was 17 years. Most of the study population had normal nutritional status. The highest degree of thrombocytopenia was in the moderate category. The results of the analysis of the relationship between nutritional status and thrombocytopenia levels obtained p> 0.05. This study concludes that there is no relationship between nutritional status and thrombocytopenia in children with DHF.